Traditional Biotechnology Content as a Media in Engaging Students with System Thinking Skills - Tri Wahyu Agustina; Nuryani Rustaman; Riandi Riandi; Widi Purwianingsih (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
Traditional Biotechnology Content as a Media in Engaging Students with System Thinking Skills. A study about how to engage students with System Thinking Skills as part of 21st century skills into Traditional Biotechnology content was conducted using Science-Technology-Religion-Engineering-Arts-Mathematics approach through one group pretest-posttest design. The study involved 43 students from 5th semester in one University determined purposively. Data were collected through system thinking test and interview format. After being collected through instruments mentioned before, data were then processed using percentage criterion n-gain on test and analyzed the result of student’s interview. Research results show 60.47% of n-gain (moderate) with the best achievement is in the ability to explain the function of each component, while the weakest achievement is in the ability to analyze the energy cycle. The result of the interview shows that the students are able to follow the lecture stages due to the repetitive and continuous assignment. The constraints found are in managing assignments within lecture time and less explored on religion aspects. Thus, Traditional Biotechnology content can facilitate students on system thinking skills.